COMPARATIVE ANALYSIS OF THE CASE SYSTEMS IN UZBEK AND GERMAN LANGUAGES - Khatamkulova Sh, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Introduction In the language system, grammatical categories are among the main tools that regulate speech. One of the most important of these categories is the case category, which  determines  the  grammatical  functions  of  nouns  in  a  sentence  and  their relationships with other words. Through cases, syntactic-semantic relations such as subject, object, possession, direction, and others are expressed. Therefore, the  case system  plays  an  important  role  in  understanding  the  grammatical  structure  of  any language.  Uzbek  and  German  belong  to  different  typological  groups:  Uzbek  is  an agglutinative language, while German belongs to the inflectional (fusional) language type. This difference is clearly reflected in the expression of case. In Uzbek, cases are mainly formed by attaching suffixes to nouns, whereas in German they are expressed through changes in articles, nouns, and pronouns. Despite these differences, in both language systems the primary function of case is to clarify grammatical relations within the  sentence  structure.  In  modern  comparative  linguistics,  comparing  structurally different languages makes it possible to identify their common and distinctive features. A  comparative  study  of  the  case  systems  in  Uzbek  and  German  is  particularly important both theoretically and practically for Uzbek-speaking learners of German. Therefore, this research aims to analyze the grammatical and functional aspects of the case category based on the two languages. The case category is not only morphological and syntactic but also a semantically and typologically significant part of the language system. Modern comparative linguistic studies show that although cases are expressed differently  across  languages,  their  primary  function  is  to  clarify  the  relationships between subject and object and to make sentence meaning clear. In Uzbek, cases are formed through an agglutinative mechanism and, together with relatively free word order, ensure semantic clarity. In German, cases interact with articles and noun forms and  are  connected  with  gender  and  number,  which  increases  morphological complexity. These aspects provide an important basis for comparative and typological analysis and help develop effective approaches for Uzbek speakers learning German.